Case report: Acquired resistance to crizotinib from a MET Y1230H mutation in a patient with non-small cell lung cancer and KIF5B-MET fusion - Dong, Su-Su; Dong, Wen; Tan, Ya-Fen; Xiao, Qiang; Wang, Tian-Li (Frontiers in Oncology, 2024)
Background: The c-met proto-oncogene (MET) serves as a significant primary oncogenic driver in non-small cell lung cancer (NSCLC) and has the potential to fuse with other genes, such as KIF5B, although it occurs infrequently. Only a limited number of reported cases have examined the clinical efficacy of crizotinib in patients with KIF5B-MET gene fusion, with no known data regarding acquired resistance to crizotinib and its potential mechanisms. In this report, we present the clinical progression of a female patient diagnosed with NSCLC and harboring a KIF5B-MET gene fusion.Case description: The patient initially exhibited partial response to first-line crizotinib treatment, albeit for a short duration and with limited efficacy. Subsequent disease progression revealed the emergence of a secondary MET mutation, specifically MET Y1230H, leading to acquired resistance to crizotinib.The reporting of this case is imperative for informing clinical practice, given the uncommon occurrence of NSCLC with MET fusion, displaying responsiveness to MET tyrosine kinase inhibitor therapy, as well as the emergence of the secondary Y1230H alteration as a potential resistance mechanism.